Training in different types of organizations : differences and dynamics in the organization of learning at work - Krogt, Ferd van der [Verfasser]; Warmerdam, John [Verfasser] (My University, 1997)
"This article focuses on differences and dynamics with respect to the organization of learning at work. It starts with a reflection on actual research perspectives on the subject of training in organizations. Four perspectives, which are currently approach, the system-oriented approach, the actor-oriented approach and the network research. We will elaborate this approach here and illustrate its potential by applying it to the analysis of training systems in two different types of organizations: bureaucratic types of organizations show remarkable differences with respect to the basic processes of their training systems: the shaping of training policies, the development of training much more organization- specific than training literature usually suggests. A network approach to training can provide a better understanding of the backgrounds of this organizational variety." (author's abstract, IAB-Doku) Mit Hilfe des 'network approach' und anhand von Fallstudien werden Aus- und Weiterbildungssysteme sowie die Dynamik und Differenzen des Lernens bei der Arbeit in zwei Typen von Organisationen (bureaucratic und professional organisation analysiert. (IAB)
Keywords: L 2.1.1 Informelles Lernen; L 2.1.3 Erfahrungslernen; S 3.2 Unternehmen und Behörden; Lernen am Arbeitsplatz; Unternehmen; Organisation